EFFECTS OF STRUCTURAL WORK OF THE FOOT WITH ALTERED SENSATION ON BALANCE DUE TO NEUROLOGICAL DAMAGE. A CASES STUDY - García Bernal, M I; González García, P; Cortés Vega, M D; Rodríguez Carrascosa, E (Cuestiones de Fisioterapia, 2009)
Introduction: proprioceptive and sole of the foot alterations have a negative effect in balance reactions. These two characteristics are found in a high number of neurological patients. Objective: to verify the effects on balance of a protocol of structural treatment of the foot in patients with ictus. Intervention: longitudinal and quantitative experimental study, with three patients with stroke. The protocol is performed in the ankle/foot with greater sensitive affectation, verifying immediately after, the change on standing balance using the dynamic balance platform Biodex. Results: better preprotocols indexes registered in the most chronic patient and also AP stability index in all patients. tocol. Greater improvement in the patient with worse initial score than in the rest (4.86 4+_ .36). Greater repercussions over standard deviation than mean stability index in the most chronic patient. Discussion/conclusion: the structural work of the foot has proved to be effective to improve the balance of the sample of this study. In acute patients, it has a greater effect on the distribution of the center of gravity, whereas in the chronic one on the oscillations of this one.